Perencanaan Strategi Pemasaran Dengan Metode Multidimensional Scalling Dan Quality Function Deployment - Aulia Asa Robbika; Teguh Baroto (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
Modern market is growing in Indonesia. In its development, the company strives to provide the best to be superior to existing competitors. Supermarket Lion Superindo is one of the supermarkets in the city of Malang, based on observations, it is known that people are still not familiar with the supermarket, so this study aims to find out what attributes required by customers, the position of the supermarket today and how where to plan the right marketing strategy to increase consumer loyalty. Positioning the company carried out using the method of Multi dimensioanl Scaling, so that it’s known that a competitor who has a lot of similarities with Lion Superindo is Giant Kawi and Loka, attributes that are considered good is the price, while the attributes of a product, place, promotion, employee, service and physical evidence still needs to be repairs / improvements. Planning strategies using Quality Function Development, this method of translating the 19 attributes that consumers desire into 28 technical response given the enterprise, so strategies are made will be in accordance with what consumers need. From planning conducted found 3 strategies that will be proposed is increasing the quality of products and services, pengembanga innovation to the concept of supermarkets and increased media information and promotional activities to consumers.